2007
DOI: 10.1128/iai.00545-07
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide fromSalmonella entericaActivates NF-κB through both Classical and Alternative Pathways in Primary B Lymphocytes

Abstract: Lipopolysaccharides (LPS) are potent polyclonal B-lymphocyte activators. Recently, we have shown that LPS inhibits both spontaneous and drug-induced apoptosis in mature B lymphocytes, through cytosolic retention of Bax, a proapoptotic protein of the Bcl-2 family, by preventing its translocation to mitochondria. Research within the last few years has revealed that members of the NF-B transcription factor regulate cell viability by activating genes involved in mitochondrion-dependent apoptosis. In this report, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
3
16
1
Order By: Relevance
“…Our findings, demonstrating that LPS can activate both classical and alternative NF-kB pathways both in primary lung epithelial cells and in lung tissue, are supported by previous work demonstrating the activation of both classical and alternative NF-kB pathways by LPS in B lymphocytes (33). Similarly, TNF-a, an agonist of the classical NF-kB pathway, has been shown to activate the alternative NF-kB pathway in murine embryonic fibroblasts (34,35).…”
Section: Discussionsupporting
confidence: 75%
“…Our findings, demonstrating that LPS can activate both classical and alternative NF-kB pathways both in primary lung epithelial cells and in lung tissue, are supported by previous work demonstrating the activation of both classical and alternative NF-kB pathways by LPS in B lymphocytes (33). Similarly, TNF-a, an agonist of the classical NF-kB pathway, has been shown to activate the alternative NF-kB pathway in murine embryonic fibroblasts (34,35).…”
Section: Discussionsupporting
confidence: 75%
“…The disorder of commensal flora is the trigger to priming the intestinal inflammation [25]. LPS is the main virulence of Gram negative bacterial and main cause to perpetuate inflammatory response [9]. TLR4 is an important pattern recognition receptor to recognize antigen and bridge innate immunity and adaptive immunity [8].…”
Section: Discussionmentioning
confidence: 99%
“…LPS is the predominant product of Gram negative bacteria and is the main ligand of toll like receptor 4 (TLR4). It is known that the intestinal mucosa immunity, in response to LPS, produces functional TLR4 and which in turn releases cytokine products to maintain the immune balance in the intestinal mucosa of the healthy animals [9]. Recent reports have demonstrated that the LPS/TLR4/NF-κB pathway plays a crucial role in the initiation and development of IBD [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…To determine if PU.1 interaction with the Nfkb1 promoter was reduced in PUB B cells, chromatin was prepared from freshly isolated and LPS-stimulated B cells and immunoprecipitated with anti-PU.1 or control Abs. WT and PUB B cells were LPS stimulated for 16 h, as this time point provided increased p50 expression upon LPS exposure (45). Relative amounts of immunoprecipitated DNA were determined by qPCR from the Nfkb1 promoter region, the positive-control Mef2c gene enhancer (13), and the negative-control Hprt gene.…”
Section: Pubmentioning
confidence: 99%